2021
DOI: 10.1038/s41467-020-20212-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical strengthening of covalent and non-covalent molecular interactions by nuclear quantum effects at finite temperature

Abstract: Nuclear quantum effects (NQE) tend to generate delocalized molecular dynamics due to the inclusion of the zero point energy and its coupling with the anharmonicities in interatomic interactions. Here, we present evidence that NQE often enhance electronic interactions and, in turn, can result in dynamical molecular stabilization at finite temperature. The underlying physical mechanism promoted by NQE depends on the particular interaction under consideration. First, the effective reduction of interatomic distanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 82 publications
(61 reference statements)
0
65
0
Order By: Relevance
“…Even relatively small molecules were shown to display nontrivial electronic effects, influencing their dynamics and allowing a better understanding of experimental observations. 161 Many other unknown chemical effects potentially wait to be discovered by studies now possible with ML-FFs. At the speed at which improvements to existing ML-FFs are published, it is not unreasonable to expect significant advances that will make similar studies possible for larger systems and help realize many more “dreams” in the near future.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Even relatively small molecules were shown to display nontrivial electronic effects, influencing their dynamics and allowing a better understanding of experimental observations. 161 Many other unknown chemical effects potentially wait to be discovered by studies now possible with ML-FFs. At the speed at which improvements to existing ML-FFs are published, it is not unreasonable to expect significant advances that will make similar studies possible for larger systems and help realize many more “dreams” in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…(mentioned earlier in the paragraph on electronic effects) investigated NQEs in small organic molecules. 161 The study revealed that NQEs can dynamically strengthen molecular interactions by enhancing n → π* donation through increasing orbital overlap, or by strengthening electrostatic interactions between neighboring charge densities (see Figure 19 C:3). Another interesting observed effect is a temporary change of bond orders, which can lead to emerging localized transient states of methyl rotors.…”
Section: Physical and Chemical Insights From Machine Learned Force Fieldsmentioning
confidence: 93%
See 3 more Smart Citations